Dakota Gold®-brand dried distiller’s grains with solubles in finishing cattle diets: a preharvest strategy against acid resistant Escherichia coli and coliforms? - C.M. Gordon; H. Thippareddi; D.L. Lambert; K. Kerr; N. Pike; J.J. Sindt; James J. Higgins; Randall K. Phebus; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2002)
Trial 1. Finishing beef heifers (345 head) were used in a 153-day finishing trial to evaluate the effects of feeding six levels of Dakota Gold®-brand dried distiller's grains with solubles (DDGS): 0%, 15%, 30%, 45%, 60%, 75% (dry basis), on the number of acid resistant E. coli and coliforms. Fecal grab samples were taken on day 65 and day 100, 2 and 20 hours after feeding, and were analyzed for acid resistant E. coli and total coliforms, as well as pH and VFA. There was a significant linear increase in fecal pH with increased DDGS at both 2 and 20 hours post-feeding (P0.05). Total fecal VFAs were not affected by dietary treatment or hour sampled after feeding (P>0.05) Trial 2. Trial 2 was conducted on ruminally fistulated Jersey steers (18 head) using three levels of DDGS (0%, 30%, 75%). Rumen and fecal grab samples were taken after 4-week adaptation periods on three occasions after every animal had been on each level of the diet and had been sampled. Fecal and rumen samples were taken 2, 4, 6, 8, 12,18, and 24 hours post-feeding. Both fecal and rumen pH were unaffected by dietary treatment, yet an hour effect was noted. Dietary treatment had no effect (P>0.05) on E. coli or total coliforms cultured from rumen fluid or feces.
Keywords: Cattlemen& #x27; s Day; 2002; Kansas Agricultural Experiment Station contribution; no. 02-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 890; Beef; E. coli; Finishing cattle; Dakota Gold brand dried distiller’s grains with solubles